Impact of parallel processing of regional anesthesia with block rooms on resource utilization and clinical outcomes: a systematic review and meta-analysis. - El-Boghdadly, Kariem; Nair, Ganeshkrishna; Pawa, Amit; Onwochei, Desire N. (Regional Anesthesia & Pain Medicine, 2020)
Block rooms allow parallel processing of surgical patients with the purported benefits of improving resource utilization and patient outcomes. There is disparity in the literature supporting these suppositions. We aimed to synthesize the evidence base for parallel processing by conducting a systematic review and meta-analysis. A systematic search was undertaken of Medline, Embase, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), the National Health Service (NHS) National Institute for Health Research Centre for Reviews and Dissemination database, and Google Scholar for terms relating to regional anesthesia and block rooms. The primary outcome was anesthesia-controlled time (ACT; time from entry of the patient into the operating room (OR) until the start of surgical prep plus surgical closure to exit of patient from the OR). Secondary outcomes of interest included other resource-utilization parameters such as turnover time (TOT; time between the exit of one patient from the OR and the entry of another), time spent in the postanesthesia care unit (PACU), OR throughput, and clinical outcomes such as pain scores, nausea and vomiting, and patient satisfaction. Fifteen studies were included involving 8888 patients, of which 3364 received care using a parallel processing model. Parallel processing reduced ACT by a mean difference (95% CI) of 10.4 min (16.3 to 4.5; p<0.0001), TOT by 16.1 min (27.4 to 4.8; p<0.0001) and PACU stay by 26.6 min (47.1 to 6.1; p=0.01) when compared with serial processing. Moreover, parallel processing increased daily OR throughout by 1.7 cases per day (p<0.0001). Clinical outcomes all favored parallel processing models. All studies showed moderate-to-critical levels of bias. Parallel processing in regional anesthesia appears to reduce the ACT, TOT, PACU time and improved OR throughput when compared with serial processing. PROSPERO CRD42018085184.